2012
DOI: 10.1016/j.renene.2012.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for stable anaerobic digestion of vegetable waste

Abstract: International trade and the market demand for pre-prepared agricultural produce is not only increasing the total quantity of waste agricultural biomass but also centralising its availability, making it potentially useful for energy production. The current work considers the suitability of vegetable trimmings and rejects from high-value produce air-freighted between Africa and Europe as a feedstock for anaerobic digestion. The physical and chemical characteristics of a typical mixed vegetable waste of this type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(62 citation statements)
references
References 32 publications
3
58
0
1
Order By: Relevance
“…Hence, the medium becomes more acidic, this acidification of the process has an adverse effect on the micro-organisms responsible for the breakdown of organic components. These findings agree with other research on anaerobic digestion (Jiang et al, 2012;Raynal et al, 1998). We can therefore infer that, if pH value falls significantly lower than the recommended pH value for anaerobic digestion, very little or no methane gas will be produced.…”
Section: Figure 2 Graphical Representations Of Vfa Values and Ph Valuessupporting
confidence: 92%
“…Hence, the medium becomes more acidic, this acidification of the process has an adverse effect on the micro-organisms responsible for the breakdown of organic components. These findings agree with other research on anaerobic digestion (Jiang et al, 2012;Raynal et al, 1998). We can therefore infer that, if pH value falls significantly lower than the recommended pH value for anaerobic digestion, very little or no methane gas will be produced.…”
Section: Figure 2 Graphical Representations Of Vfa Values and Ph Valuessupporting
confidence: 92%
“…Sin embargo, el rendimiento de la producción de metano se puede ver afectado por la presencia de un alto porcentaje de proteínas ya que podrían ser responsables de la baja biodegradabilidad del residuo debido a los productos intermedios de su degradación [27]. En cuanto a los residuos vegetales de algunos cultivos, los elevados valores de C/N y la escasez de elementos traza pueden afectar el correcto desarrollo del proceso por la producción de ácidos grasos y el decrecimiento del pH del sistema [32].…”
Section: Identificación Del Potencial De Biogás Por Residuounclassified
“…A study by Jiang [33] showed that vegetable waste was not suitable for use as a sole substrate for AD without the addition of trace elements due to the rapid build-up of volatile acids, which can result in a significant decrease in pH within the reactor which can in turn stress and inhibit the activity of methanogenic bacteria [32].…”
Section: Food Wastesmentioning
confidence: 99%